PROGRAM APOTEK HIDUP SEBAGAI MEDIA PENANAMAN NILAI SOSIAL DALAM MENUMBUHKAN SIKAP GOTONG ROYONG SISWA DI SMA NEGERI 1 LABUAPI - Yusni Febrian; Rista Hilda; Hairil Wadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
He Living Pharmacy Program is an environment-based activity utilized as a medium for instilling social values ​​in students. This activity aims to instill social values ​​and foster a spirit of mutual cooperation in students through the Living Pharmacy Program at SMA Negeri 1 Labuapi. This method includes planning, outreach, implementation, and evaluation, with students actively involved in creating and maintaining the living pharmacy garden. Data collection was conducted through observation to assess changes in students' social attitudes during the activity. The results of the activity indicate an increase in students' mutual cooperation, characterized by cooperation, responsibility, and social awareness. The program also provides contextual, environment-based learning experiences. Thus, the Living Pharmacy Program is effective as a medium for instilling social values ​​in schools.